Introduction of Energy Efficient Technologies in the Livestock Complex of Ukraine - ZAKHARCHENKO, Oleg V.; YEVDOKIMOVA, Olha M.; KOLODYNSKYI, Sergii B.; SMELIANETS, Tetiana V.; BILEHA, Olena V. (Journal of Advanced Research in Law and Economics; Vol 9 No 6 (2018): JARLE Volume IX Issue 6(36) Fall 2018, 2019)
Opportunities for the development of animal husbandry are based on economic, logistic and environmental components that form the development and competitiveness of livestock products on the international market. To do this, we should follow the leading major tendencies in order to improve the efficiency of livestock farms. The article presents the main directions for improving the efficiency of the livestock complex on the basis of mathematical modeling and the economic calculation of performance indicators. The authors chose indicators that are recognized in the international environment as parameters of effectiveness. In particular, the article considers the possibility of reducing the energy consumption by an enterprise as an international indicator, and also forms a holistic economic assessment, which is built on the perception of the need to increase the level of operation. The branch of milk production is chosen as the object of study, as it is most subject to competition not only from traditional producers of milk, but also from producers of its substitutes. The article presents calculations of the yield of products, their energy and weight categories, and also determines the reduction of energy consumption for the milk-producing complex as a whole. A model calculation is given for the practical application of the benefits of reducing energy costs during the modernization of the complex, and not its complete restructuring. The authors think that the further guidelines of development of the studied problem is to bring these indicators to a single indicator of effectiveness in the international technical and economic environment.